Audiências de custódia e encarceramento de mulheres pelo tráfico de drogas: análise de audiências ocorridas na cidade de João Pessoa sob olhares criminológicos feministas - Mendonça, Karoline Henrique (2019)
This research aims to investigate whether gender aspects influence the criminalization of women accused of committing drug trafficking in the city of João Pessoa. Initially, we started from the problematic phenomenon of the increasing incarceration of women in Brazil, which has experienced a rise of almost 660% in the last 16 years, and drug trafficking is the main crime they are accused of in more than half of the cases. The changes brought by the law nº 11.343/06, with the increase of punitivism towards people defined as traffickers, had a special and harmful impact on women. This phenomenon may be better understood if we take into consideration the roles essentially assigned to this group in the trafficking chain – typically subordinate and more exposed to the action of state punitive power – as well as the structural conjuncture of society that places women in more vulnerable socioeconomic positions. Given this scenario, with the implementation and consolidation of Bail Hearing procedures in João Pessoa, we found an opportunity to deepen the analysis of the criminalization of women accused of drug trafficking through a Field Research. In this context, the feminist contributions to criminology makes it possible to problematize the current drug policy and identify the selective and discriminatory way that the criminal system acts, mainly affecting women. In this context, the feminist perspective is introduced in the study of the gender category as another element that integrates the criminal selectivity of female population, and in the analysis of “feminization of poverty”, which helps to understand the socioeconomic and gender vulnerability of women. The predominant approach method in this research is the inductive one, since it was made a previous confrontation with the investigated reality and a subsequent interpretation with the help of the adopted theoretical bases. The research techniques were documentary and bibliographical research and direct documentation. As for the empirical part of the research, we conducted a descriptive and explanatory investigation. Descriptive because we initially sought to detail and describe essential characteristics about the problem investigated, as well as establishing variables that helped in understanding it. As for the explanatory aspect, it appears as we seek for the answer to the research problem that drives this investigation, that is, if aspects related to gender influence the criminalization process of these women. In the field, we observed 93 Bail Hearings, most of which took place during 2018. We concluded, after conducting the research, that gender elements play a role in the criminalization process of these women, which, in the context of the Bail Hearings, manifested itself in paternalistic arguments made by prosecutors and judges, moral lectures, judgments about their personal life, evading the legally relevant elements and intruding on their private lives. In addition, we noted the determining influence of motherhood on the outcome of the hearings. Notwithstanding the recognition of the right to liberty or to house arrest due to the legal provision in art. 318 of the CrPC, we noted that the granting of provisional release or house arrest, in some cases, depended on a non-legally based trial, which concerned the gender roles imposed on these women and which they should play in order to have their motherhood recognized. When such a performance was not sufficiently clear to the judges and the prosecutors, the patriarchal judgment overlapped, leading to non-recognition of their freedom.